Efektivitas Friction Massage Dalam Mengurangi Nyeri Punggung Pasca Kemoterapi Pada Pasien Kanker Serviks Di RSUD Dr. Saiful Anwar Malang - Febriyanita Ariyati; Yuliyanik .; Senditya Indah Mayasari (LPPM Widyagama Husada Malang, 2026)
Abstract Back pain is a common physically distressing side effect reported by cervical cancer patients undergoing chemotherapy, impacting their adherence to treatment and quality of life. This study aims to determine the effectiveness of Friction massage in reducing post-chemotherapy back pain among cervical cancer patients at the Singkarak Room of Dr. Saiful Anwar Hospital, Malang. A Quasi-Experimental design with a One-Group Pretest-Posttest approach was employed. A sample of 25 respondents was selected using accidental sampling based on specific inclusion criteria. Data on pain intensity were measured using the Numeric Rating Scale (NRS) before and immediately after a 20-minute Friction massage intervention, then analyzed using a paired t-test. The results showed that before the intervention, 76% of respondents experienced mild pain and 24% had moderate pain. After the Friction massage, 68% reported no pain and 32% reported mild pain. The paired t-test obtained a significant value (p = 0.001, < 0.05), indicating that H1 is accepted. In conclusion, Friction massage is an effective non-pharmacological complementary modality for reducing post-chemotherapy back pain in cervical cancer patients. Clinical implementation of this intervention as a standard nursing care protocol is highly recommended to improve patient comfort.